2015
DOI: 10.1007/s00401-015-1495-z
|View full text |Cite|
|
Sign up to set email alerts
|

Gliomatosis cerebri: no evidence for a separate brain tumor entity

Abstract: Gliomatosis cerebri (GC) is presently considered a distinct astrocytic glioma entity according to the WHO classification for CNS tumors. It is characterized by widespread, typically bilateral infiltration of the brain involving three or more lobes. Genetic studies of GC have to date been restricted to the analysis of individual glioma-associated genes, which revealed mutations in the isocitrate dehydrogenase 1 (IDH1) and tumor protein p53 (TP53) genes in subsets of patients. Here, we report on a genome-wide an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
79
3
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(92 citation statements)
references
References 24 publications
8
79
3
1
Order By: Relevance
“…Management recommendations for these NOS categories are included in Table 1, but evidence is low. Oligoastrocytomas and gliomatosis cerebri both lack distinctive genetic and epigenetic profiles 11,12 and are thus no longer considered as distinct glioma entities. 1 Diffuse midline glioma, H3-K27M-mutant, has been introduced as a novel entity characterized by midline tumor location and presence of lysine to methionine mutation at codon 27 of histones 3.3 or 3.1.…”
Section: Histological Classification and Molecular Diagnosticsmentioning
confidence: 99%
“…Management recommendations for these NOS categories are included in Table 1, but evidence is low. Oligoastrocytomas and gliomatosis cerebri both lack distinctive genetic and epigenetic profiles 11,12 and are thus no longer considered as distinct glioma entities. 1 Diffuse midline glioma, H3-K27M-mutant, has been introduced as a novel entity characterized by midline tumor location and presence of lysine to methionine mutation at codon 27 of histones 3.3 or 3.1.…”
Section: Histological Classification and Molecular Diagnosticsmentioning
confidence: 99%
“…The degree of involvement of gray and/or white matter also varies among affected patients [5]. Finally, it remains uncertain whether GC represents a separate clinical and molecular entity or simply represents the extreme spectrum of infiltrative gliomas [8, 12]. Because of its rarity and the lack of suitable tissue [8], molecular analysis of GC in adults consisted mostly of targeted gene sequencing and copy number abnormalities [7, 11, 12, 17, 19, 21, 25, 28].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it remains uncertain whether GC represents a separate clinical and molecular entity or simply represents the extreme spectrum of infiltrative gliomas [8, 12]. Because of its rarity and the lack of suitable tissue [8], molecular analysis of GC in adults consisted mostly of targeted gene sequencing and copy number abnormalities [7, 11, 12, 17, 19, 21, 25, 28]. A recent study, which utilized DNA methylation analysis to assess molecular subgroups and copy number abnormalities, reported that GC in adults was not a distinct molecular entity because its genetic and epigenetic characteristics resembled those found in other high-grade gliomas [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The term "diffuse glioma" is currently used to describe as a special neoplastic pattern indicating a widespread brain invasion involving three or more cerebral lobes, frequent bilateral growth and possible extension to infratentorial structures, common to different glioma subtypes The term "gliomatosis", formerly used in these cases, has been recently dismissed in the 2016 WHO classification (1,2). Here, we discuss the presentation and diagnosis of a diffuse glioblastoma in a young male who was initially suspected of having acute hemorrhagic leukoencephalitis (AHLE), a variant of acute disseminated encephalomyelitis (ADEM), and highlight the need of a synergic radiological and histological work-up to reach a correct diagnosis.…”
Section: Introductionmentioning
confidence: 99%